HUBUNGAN LAMA PENGGUNAAN GADGET DENGAN INTERAKSI SOSIAL MAHASISWA DI PEKANBARU RIAU - Saniya Saniya; Faikkotul Munawaroh (LPPM Universitas Abdurrab, 2025)
Abstract Gadgets are devices that are communication tools and are widely used in everyday life, whether used as a communication tool or to help with work. Social interaction is a dynamic social relationship between individuals and individuals, groups and groups and individuals and groups. Excessive use of gadgets will have an impact on social interaction patterns between individuals. The aim of this research is to determine the relationship between length of use of gadgets and social interaction among students at the Faculty of Pharmacy and Health Sciences, Abdurrab University, Pekanbaru.